(untitled) (International Journal of Geoscience, Engineering and Technology, 2024)
The records of impacts resulting from disasters in risk areas point to the urgent need for protection measures, given that the prevention of this occurrence requires joint actions, especially for those involving civil protection, housing, infrastructure, education and health. However, human interventions and natural hazards collaborate to destabilize the soil and increase the degree of a phenomenon that causes adverse effects. In this context, this research aims to identify and classify the degree of risk in isolated points located in the central intermediates of the municipality of Teófilo Otoni, in the state of Minas Gerais, where there are signs of landslides. These points are located on Rua Riccioti Míglio (Point 1 and Point 2), in the Ipiranga neighborhood, and on Rua Minervino de Castro Pinto (Point 3), in the Centro neighborhood. The method used takes into account the availability of an emergency landslide risk registration script, made available by the Ministry of Cities to determine the degree of risk of the occurrence of land mass movement. The study involves the analysis of Point 1, Point 2 and Point 3, which were classified with risk level R4, falling into very high risk areas, and stabilization and safety measures must be taken. With regard to the occupation of urban territorial spaces under development, such as in the municipality of Teófilo Otoni, there is a lack or inefficiency in the application of norms aimed at monitoring the use and occupation of areas classified as at risk.